Choosing an effective food classification system for promoting healthy diets in Thailand: a comparative evaluation of three nutrient profiling-based food classification systems (government, WHO, and Healthier Choice Logo) and a food-processing-based food classification system (NOVA) - Phulkerd, Sirinya; Dickie, Sarah; Thongcharoenchupong, Natjera; Thapsuwan, Sasinee; Machado, Priscila; Woods, Julie; Mo-Suwan, Ladda; Prasertsom, Piyada; Ungchusak, Chantana; Khitdee, Chiraporn; Lawrence, Mark (Frontiers in Nutrition, 2023)
This study aimed to assess the nutritional quality of food and beverage products in Thailand by comparing four different food classification systems: the nutrient profiling-based food classification systems by the Department of Health (DOH), the WHO South-East Asia Region (WHO SEA) and the Healthier Choice Logo (HCL), and the food processing-based food classification system, NOVA. This study used secondary data from the Mintel Global New Products Database (N=17,414). Food subgroups were classified differently based on these four systems. The DOH classified food products into three groups: Group A - healthy pass or meeting standard; Group B - not meeting standard; and Group C – far below standard. The WHO SEA classified food products into two groups: marketing prohibited products; and marketing permitted products. The HCL classified food products into two groups: eligible products for the logo; and ineligible products for the logo. The NOVA classified food products into four groups: unprocessed or minimally processed foods (MP); processed culinary ingredients (PCI); processed foods (P); and ultra-processed foods (UPF). Descriptive statistics (percentage and frequency) were used for analysis. Agreement analysis was conducted using Cohen’s Kappa statistic between each pair of food classification systems. Of the total sample which could be classified by any of the four classification systems (n=10,486), the DOH, WHO SEA and HCL systems classified products as healthy (Group A, marketing permitted or eligible for HCL logo) at 10.4%, 11.1% and 10.9%, respectively. Only 5.6% were classified as minimally processed foods using NOVA and 83.1% were ultra-processed foods (UPFs). Over 50% of products classified as healthy by the nutrient profiling systems were classified as UPF according to the NOVA system. Products which were eligible for the HCL had the highest proportion of UPF products (84.4%), followed by the Group A products (69.2%) and the WHO marketing permitted products (65.0%), respectively. A hybrid food classification approach taking both nutrients and food processing into account is needed to comprehensively assess the nutritional quality of food and beverage products in Thailand.